Literature Review: Disaster Education for Students and Its Challenges - Dakwan Soaloon Harahap (Faculty of Medicine University of Malikussaleh, 2024)
This research aims to determine the effect of disaster education on students' disaster preparedness and challenges in implementation. The research method used is literature review or library research by searching for reference data via the Google Scholar search engine. Based on literature review data, it is known that disaster education is successful in increasing students' preparedness for disasters. This was found from several references which found that there was an increase in students' knowledge of natural disasters after receiving disaster education. There are also challenges in disaster education which are divided into two types, namely internal challenges and external challenges. Internal challenges come from within the organizer of disaster education, in this case the school environment, while external challenges come from outside the school that provides disaster education.